Pengaruh Kecanggihan Teknologi Informasi, Kemampuan Teknik Pemakai, Dan Dukungan Manajemen Puncak Terhadap Kinerja Sistem Informasi Akuntansi (SIA) - Made Artha Wiyoga; Cokorda Gde Bayu Putra (UNHI Press, 2022)
Thisstudy aims to tell how theinfluence of InformationTechnology Sophistication,User Technical Ability andTop ManagementSupport on Accounting InformationSystem Performance.This research has beenconducted at BPR inDenpasar Region.Where the sample in this studyamounted to 147employees who areinvolved in the useof accounting information systems.The sampling methodused in thisresearch is purposivesampling.Based on theanalysis test results, it isknown that the influenceof InformationTechnology Sophistication, UserTechnical Abilityand TopManagement Supporthas a positiveand significant effect onAccounting InformationSystem Performance